Strengthening Collaboration through Perception Alignment: Hybrid Workplace Leadership Impact on Member Awareness, Understanding, and Learning Agility - Darmawan Tri Nugroho; Pri Hermawan (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2022)
The recent development of cross-functional project initiatives and implementation of remote technology applications is changing the leader and team member working environment that influences their interaction and collaboration with other teams/customers/stakeholders/ providers/any related parties to compete in the rising digitalization and VUCA (volatility, uncertainty, complexity, and ambiguity) situation. This research wants to dissect how the influence of hybrid workplace leadership capabilities on the awareness, understanding, and learning agility of cross-functional project team members to foster team perception alignment and achieve strengthened collaboration. Researcher dissects individual team members' mental processes (awareness of the intended purpose, understanding of self-others, and learning agility) that connect leadership capability and team perception alignment to enhance collaboration during hybrid workplace implementation. This study is a quantitative research methodology, collecting data through a questionnaire survey and then analyzing data from 99 respondents using Partial Least Squares Structural Equations Model (PLS-SEM). Based on the result of this study, hybrid workplace leadership impacts the awareness of purpose. Then awareness affects the understanding of self and others, and both affect the learning agility of each team member, which influences the alignment of perceptions in the work team. This alignment of perceptions contributes to the collaboration process with other teams/organizations.